Breeding progress reduces carbon footprints of wheat and rye. (1st December 2022) - Riedesel, L.; Laidig, F.; Hadasch, S.; Rentel, D.; Hackauf, B.; Piepho, H.-P.; Feike, T.
Abstract: Crop breeding has boosted global agricultural productivity over recent decades, but little is known about its contribution to climate change mitigation. Here we assess greenhouse gas emissions per unit land (GHGL) and greenhouse gas emissions per unit harvest product, i.e. carbon footprint (CFP) of winter wheat ( Triticum aestivum ) and winter rye ( Secale cereale ) from official German variety trials in the period 1983 to 2019. We assess the life cycle greenhouse gas (GHG) emissions and analyze the data using mixed effects models. We find that breeding progress led to slightly increased GHGL, amounting to ∼4–10%, but to strongly decreasing CFP, amounting to ∼13–23% in wheat and rye since 1983. With a ∼20% lower GHGL and ∼8% lower CFP in rye compared to wheat, the extension of rye production offers viable climate change mitigation potential. Finally, we find that lower CFP are associated with hybrid breeding, chemical plant protection and larger farms. We conclude that with increasing global food demand and limited cropland, breeding progress contributes considerably to climate change mitigation through reduced CFP. Highlights: First evidence on the contribution of breeding progress to climate change mitigation. 27, 652 and 10, 523 Genotype x Environment x Management-combinations of wheat and rye. Rye has lower greenhouse gas emissions (∼20%) and carbon footprint (∼8%) than wheat. Crop breeding decreased carbon footprint in wheat and rye by ∼13–23% since 1983/1985.